The Relationship between Digital Literacy and Communication Ethics among Generation Z on Social Media - Dellia Safitri; Desriyeni Desriyeni (Darul Yasin Al Sys, 2026)
The rapid advancement of digital technology and the intensive use of social media among Generation Z have raised significant concerns regarding digital communication ethics. Although digital literacy is considered an important factor in shaping ethical communication behavior, empirical studies examining this relationship, particularly among university students, remain limited. This study aims to determine the level of digital literacy, the level of communication ethics, and the relationship between digital literacy and communication ethics among Generation Z social media users at the Faculty of Languages and Arts, Universitas Negeri Padang. A quantitative approach with a correlational design was employed. The sample consisted of 98 respondents selected through stratified random sampling. Data were collected using questionnaires and analyzed using descriptive statistics and Spearman correlation tests. The findings indicate that both digital literacy and communication ethics are categorized as good, and that a strong correlation exists between digital literacy and communication ethics among Generation Z social media users. This suggests that higher levels of digital literacy are associated with better ethical communication in digital interactions. The study concludes that digital literacy plays an important role in supporting ethical social media communication. Its contribution lies in emphasizing the need to strengthen digital literacy programs integrated with communication ethics development in educational settings to promote more responsible digital behavior.